Analisis Pemasaran Tandan Buah Segar Kelapa Sawit Kecamatan Putri Hijau, Kabupaten Bengkulu Utara - Sumartono, Eko; Suryanty, Melly; Badruddin, Redy; Rohman, Agus (AGRARIS: Journal of Agribusiness and Rural Development Research, 2018)
The sale of fresh fruit bunches in Putri HijauÂ sub-district has variety of marketing channels from farmers to consumers. The diversity of marketing channels should result inÂ differences in the price levels received byÂ farmers and the costs incurred by each marketing agency, such as freight costs, transportation costs to factories, fruit shrinkageÂ costs, and other costs. This study aims toÂ identify marketing channels and compareÂ the marketing channel efficiency of freshÂ fruit bunches (TBS) of palm oil formed inÂ Kecamatan Putri Hijau, North Bengkulu.Â Determination of farmer respondents isÂ done by purposive sampling counted 41Â people, and marketing agency respondentsÂ use snowball sampling method. The resultsÂ showed that there are three channels ofÂ marketing of oil palm FFS formed, namelyÂ Channel I (farmers - collector traders - factories), Channel II (farmers - farmerÂ groups - factories), Channel III (farmers - factories). The most widely used channels by farmers are channel I (farmers - collectors â mills) that have the highestÂ margin and low farmerâs share. The merchandise margin and the profit-to-costÂ ratio indicate that only marketing channel I in Bani Village is efficient. MarketingÂ channel I in Desa Bani Village has a marketing margin value of Rp206/kg withÂ the value of profit to marketing cost ratio of 1.17.